Peningkatan Literasi Akuntansi Digital bagi Siswa SMK melalui Penerapan Pembelajaran Berbasis Teknologi Informasi - WIJAYA, JULI RIYANTO TRI (Universitas Negeri Gorontalo, 2025)
This research aims to improve digital accounting literacy for vocational high school students through the implementation of information technology-based learning. The background of this research is based on the development of the digital era, which increasingly demands new skills in accounting. The use of software, accounting applications, and an understanding of digital concepts are becoming essential competencies for vocational high school graduates. This community service activity was conducted at SMK NU Kramat as a one-day socialization focused on understanding the basics of digital accounting, the use of information technology in recording transactions, and an introduction to digital-based accounting applications. The implementation method involved material presentations, interactive discussions, and simple exercises that directly involved students. The results showed that students were highly enthusiastic and active in participating in the activity because the material presented was relevant to their needs. Students gained a new understanding of the importance of digital accounting literacy as preparation for the world of work. This improvement was evident in the positive response, active participation, and students' ability to answer questions and complete exercises related to digital accounting. This activity demonstrated that information technology-based learning can be an effective strategy for improving digital accounting literacy among vocational high school students. Therefore, this community service is expected to be the first step in fostering the readiness of the younger generation to face the digital transformation in accounting and can serve as a model for implementing similar learning in other vocational schools.